Inventário extrajudicial do companheiro: a sucessão na união estável - Depieri, Rafael Vitelli (2021)
In view of the study that was guided on the theme about the succession of companions within the extrajudicial inventory, it was sought at this time to result in the research used under the parameters not only social, but legal and economic on the succession law in Brazil and the verification of laws of Europe, Central America (Mexico) and Latin America compared to what has been agreed in the Brazilian legal system since the deal present in the Civil Code of 2016 until now with innovations based on the decisions of the Supreme Federal Court. The methodology used for this dissertation was based on a qualitative analysis in a bibliographic review, verifying laws, doctrines, jurisprudence, and comparing the works and the method in a heterogeneous analysis for the subsequent conclusions. Divided into four chapters, it initially presented the previous and current legislation dealing with the family institute in Brazil; after the succession law was analyzed and what are the measures taken by the indoctrinators to understand about the insertion or not the partner in a comparative and egalitarian position with the spouse; and reaching the focus on verifying the extrajudicial inventory and the deal with the administrative action that will be taken. Under the scenario that found the dissonant positions present in the Brazilian doctrines, the focus given to the work began to delimit the contours that exist between each position on the operators of law chosen for the wide research in bibliographic review that inserted the present work. Thus, with what we had from the deal to offer a general overview of what is understood for and against the insertion of the partner under the same deal that occurs with the spouse when talking about opening the succession and how they are divisions of assets between rights and duties are made based on different understandings